Optimization of Monoclonal Antibodies Purification Expressed in H-192 cells using Preparative Native-Polyacrylamide Gel Electrophoresis - Santhana, Krishnan; Zularisam, A. W.; Chua, Gek Kee; Chew, Few Ne; Mimi Sakinah, A. M. (Hibiscus Publisher, 2015)
Monoclonal antibodies (mAbs) are unique and specific drug molecules targeting the treatment of various diseases such as arthritis, immune disorders, infectious diseases, and cancer etc. Different methods such as antibody coupled affinity chromatography, hydrophobic interaction chromatography, etc., can be applied to purify mAbs from various sources. This article provides a simple, cost effective, preparative native-polyacrylamide gel electrophoresis (n-PAGE) technique to purify mAbs expressed in H-192 cells (Hybridoma murine cell lines) against an antigen i.e. 17-alpha-hydroxyprogesterone (17-OHP), which further can have diagnostic application to detect Congenital Adrenal Hyperplasia (CAH). Furthermore, different parameters such as concentration and volume of the feedstock (medium containing antibodies), pore size of gel, height of resolving gel etc. were optimized to obtain the maximum purity and yield of mAbs.